Effect of Dietary Chestnut or Quebracho Tannin Supplementation on Microbial Community and Fatty Acid Profile in the Rumen of Dairy Ewes. (31st December 2017) - Buccioni, Arianna; Pallara, Grazia; Pastorelli, Roberta; Bellini, Letizia; Cappucci, Alice; Mannelli, Federica; Minieri, Sara; Roscini, Valentina; Rapaccini, Stefano; Mele, Marcello; Giovannetti, Luciana; Viti, Carlo; et al.
Abstract : Ruminants derived products have a prominent role in diets and economy worldwide; therefore, the capability to control the rumen microbial ecosystem, for ameliorating their quality, is of fundamental importance in the livestock sector. The aim of this study was to evaluate the effect of dietary supplementation with chestnut and quebracho tannins on microbial community and fatty acid profile, in the rumen fluid of dairy ewes. Multivariate analysis of PCR-DGGE profiles of rumen microbial communities showed a correlation among the presence of chestnut or quebracho in the diet, the specific Butyrivibrio group DGGE profiles, the increase in 18:3 cis 9, cis 12, and cis 15; 18:2 cis 9 and cis 12; 18:2 cis 9 and trans 11; 18:2 trans 11 and cis 15; and 18:1 trans 11 content, and the decrease in 18:0 concentration. Phylogenetic analysis of DGGE band sequences revealed the presence of bacteria representatives related to the genera Hungatella, Ruminococcus, and Eubacterium and unclassified Lachnospiraceae family members, suggesting that these taxa could be affected by tannins presence in the diets. The results of this study showed that tannins from chestnut and quebracho can reduce the biohydrogenation of unsaturated fatty acids through changes in rumen microbial communities.